Vitamin B12 deficiency in pregnancy and its association with maternal and fetal outcomes - Jahan, Noor; Fatema, Kaniz; Das, Tripti Rani; Pervin, Hasna Hena; Sharmin, Riffat Ara; Majumder, Dipika; Islam, Fahmida; Tamanna, Tabassum; Nessa, Meherun (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Pregnancy is a unique physiological state characterized by profound changes in a woman’s body to support fetal growth and development. Adequate nutrition is vital during pregnancy to meet the increased demands of both the mother and the developing fetus. Among the various nutrients required during pregnancy, vitamin B12 stands out as a critical micronutrient. It plays a pivotal role in cellular replication, neurodevelopment, and the synthesis of DNA, making it essential for the proper growth and development of the fetus. This study was conducted to evaluate vitamin B12 deficiency in pregnancy and its association with maternal and fetal outcomes. Methods: This was a cross-sectional study conducted among consecutively selected pregnant women who had just given birth to a single live baby admitted to the department of obstetrics and gynecology and also the department of feto-maternal medicine, Bangabandhu Sheikh Mujib medical university (BSMMU), Shahbagh, Dhaka from September 2022 to August 2023. A total of 90 women of 18-40 years of age at their 28-40 weeks of gestation were included in this study. Study subjects with vitamin B12 levels of <200 pg/ml were considered as the low level (group I), whereas level ≥200 pg/ml was considered as the normal (group II). Observations were undertaken on pregnancy complications and perinatal outcomes, which were compared between the two groups. Results: The study revealed majority (57.8%) of the study participants age were within 26-34 years, a housewife was 74.4% and multigravida constituted 70.0% of the respondents. The 31 (34.4%) of the respondents had vitamin B12 level below 200 pg/mL and 59 (65.60%) women had normal serum vitamin B12 levels (≥200 pg/mL). Congenital hydrocephalus was observed in 16.1% of the group I mothers compared to only 1.7% in group II (p=0.017) and neural tube defect was present in 9.7% of group I but in none of group II mothers (p=0.038). Conclusions: Mothers having vitamin B12 deficiency experience significantly higher rates of oligohydramnios, fetal hydrocephalus, and neural tube defects compared to those with normal vitamin B12 levels. However, there was no significant maternal complication.